Strategi Supir Angkot Bertahan Dalam Menghadapi Persaingan Taksi Online Dalam Perspektif Ekonomi Islam - Hendro Prabowho, Trimuji; Adetio Setiawan, Romi; Afrida Indra, Yetti (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
The purpose of this research is to understand the application of Islamic economic principles by public transportation drivers in Bengkulu City, with the expectation that they can effectively compete with online taxis. Additionally, this study aims to comprehend how these drivers can meet their daily needs amid the increasing popularity of online taxis. The research employs a qualitative descriptive method, with data collected through questionnaires, interviews, and documentation. The gathered information is analyzed using selection, summarization, presentation, and conclusion-drawing techniques. The research findings indicate that some public transportation drivers do not adhere to Sharia economic principles due to a lack of understanding of their application in the Islamic context. One of the informants interviewed said that there were still drivers who set rates that were considered excessive, contradicting Islamic values that prohibit actions harmful to passengers. Furthermore, the study reveals the absence of a specific method currently utilized by public transportation drivers to attract passengers. The primary target demographic for these drivers appears to be mothers wanting to go to the market and schoolchildren, possibly due to their limited understanding of utilizing online taxis.